Nicaea and the Analytic Unfolding of Divine Sonship - Sanders, Fred (Reformed theological review, 2025)
The doctrine of eternal generation sometimes draws the objection that it sounds like it is covertly telling a story about how the Son came to be. This objection, called here the story objection, can be answered in several ways. Trinitarian theology will never be able to preempt the raising of the story objection, because Scripture itself reveals the second person as the Son, and the Nicene Creed rightly models the classical theological practice of unfolding that revealed term by the use of action verbs: if Son, then generated. Thomas Aquinas is a key example of a trinitarian theologian who accepts both the biblical name and its Nicene unfolding as action that does not reduce to story.